Troponin measurement for risk stratification after cytoreductive surgery. Issue 9 (22nd June 2021) - Vacheron, C.-H.; Lambert, A.; Fauvernier, M.; Vassal, O.; Wallet, F.; Bakrin, N.; Vaudoyer, D.; Kepenekian, V.; Passot, G.; Glehen, O.; Piriou, V.; Friggeri, A.
Abstract : Several studies have raised interest in the use of postoperative troponin levels to stratify risk of postoperative morbidity and mortality. In this study, postoperative troponin concentration after cytoreductive surgery (with or without hyperthermic intraoperative intraperitoneal chemotherapy) was associated with severe postoperative complications, and enhanced the predictive capability of a multivariable model focusing on postoperative complications.